2009
DOI: 10.2106/jbjs.g.01613
|View full text |Cite
|
Sign up to set email alerts
|

Humoral Factors Enhance Fracture-Healing and Callus Formation in Patients with Traumatic Brain Injury

Abstract: Patients with a severe brain injury release unknown humoral factors into the blood circulation that enhance and accelerate fracture-healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 21 publications
2
68
0
1
Order By: Relevance
“…Discussion W e previously demonstrated that patients with a traumatic brain injury and a femoral shaft fracture have enhanced fracture-healing, with a twofold shorter time to union and increased callus formation compared with patients with a femoral fracture but no traumatic brain injury 13 . Proteomic investigations have demonstrated a change in the profile of serum and cerebrospinal fluid proteins in response to traumatic brain injury that is potentially linked to the osteogenic influence that traumatic brain injury has on fracture-healing 33 .…”
Section: Serum Supports Mineralization Of Skeletal Muscle Cellsmentioning
confidence: 88%
See 1 more Smart Citation
“…Discussion W e previously demonstrated that patients with a traumatic brain injury and a femoral shaft fracture have enhanced fracture-healing, with a twofold shorter time to union and increased callus formation compared with patients with a femoral fracture but no traumatic brain injury 13 . Proteomic investigations have demonstrated a change in the profile of serum and cerebrospinal fluid proteins in response to traumatic brain injury that is potentially linked to the osteogenic influence that traumatic brain injury has on fracture-healing 33 .…”
Section: Serum Supports Mineralization Of Skeletal Muscle Cellsmentioning
confidence: 88%
“…Several groups of investigators, including ours, have suggested the importance of humoral factors in the cascade of events leading to heterotopic ossification on the basis of in vitro studies demonstrating the mitogenic and osteogenic effects of serum from subjects who had undergone trauma to the central nervous system [11][12][13][14][15][16] . These investigators used models of osteoblasts, mesenchymal stem cells, and fibroblasts, but none reviewed the effect of serum from patients with traumatic brain injury on cells derived from skeletal muscle.…”
mentioning
confidence: 99%
“…The results of the current study show that osteoblasts have been found in abundance and often, in the majority of the debris of intra-medullary reaming of femur and tibia in patients with associated severe head injury with and these fractures healed rapidly with exuberant union callus without delayed union or nonunion that may reflect that certain mechanism has prepared the fracture environment in these patients with plenty of osteoblasts from local bone marrow and fractures ends and may also form undifferentiated mesenchymal cells of distant bone marrow, which have been homed to fracture site and differentiated into osteoblasts to appear in the reaming debris and to induce adequate and faster healing. 25,26,31 …”
Section: Discussionmentioning
confidence: 99%
“…Accelerated fracture healing occurs in a significant percentage of patients with traumatic brain injury [1][2][3][4][5][6][7]. Heterotopic ossification in the connective tissue around joints is sometimes also seen [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Heterotopic ossification in the connective tissue around joints is sometimes also seen [8][9][10]. Though different hypotheses have been reported, a common unified explanation for this phenomenon has not been documented [7,[11][12][13][14][15]. One view is that traumatic brain injury allows growth factors that promote bone growth to pass from the brain into the systemic circulation.…”
Section: Introductionmentioning
confidence: 99%